Draco defensor. O pozytywnych konotacjach symboliki smoka w heraldyce miejskiej. Przykład Żmigrodu .......... 315 (Fantastyczne stwory i bestie w dziejach i kulturze od antyku po czasy najnowsze, 2025)
DRACO DEFENSOR. ABOUT THE POSITIVE CONNOTATIONS OF DRAGON SYMBOLISM IN URBAN HERALDRY. THE EXAMPLE OF THE TOWN OF ŻMIGRÓDIn 2021, the local government authorities made a correction to the coat of arms of the city and municipality of Żmigród. The previous dragon, crushed by a tower crowned with a cross, was replaced by a dragon passing through the city gate, which at the top was decorated with a sphere instead of a cross. This change caused resistance from the local community. They accused the authorities of devaluing the symbolic meaning of the coat of arms and glorifying unclean powers. The previous coat of arms, according to the city’s residents functioning in this form since always, has been unequivocally interpreted as a symbol of God’s victory over Satan and evil. Research conducted by the author of the article showed that the image of a dragon crushed by a tower did not appear until the 17th century. However, the tower was then decorated with a sphere, not a cross, which was incorporated into the coat of arms of Żmigród, based on modern iconography, only at the end of the 19th century by Otto Hupp, an outstanding German heraldist and designer of coats of arms. The oldest emblem of Żmigród was the image displayed on the oldest municipal seal of Żmigród from 1402, which the local government authorities used as a model while working on changing the coat of arms. It depicts a dragon passing through a city gate crowned with a sphere. Analyzing the signs of the dragon’s presence in the broadly understood culture of the era, e.g. on the seals of the Czersk princes, in urban heraldry, Arthurian legends or the nomenclature and emblems of the Order of the Dragon, the author shows that in addition to the clearly negative connotation of the symbolism of this monster, strongly perpetuated by the Church, it also had positive connotations in the Middle Ages. In secular tradition, it was considered a symbol of strength, courage and vigilance. This is also how he interprets the symbolic meaning of the oldest coat of arms of Żmigród, concluding that the Żmigród dragon is a kind of draco defensor standing guard over the safety of the city and its inhabitants, and today also – after replacing the sphere on the top of the tower with the cross in the new coat of arms in 2022 – of the Catholic faith and religious values.